Managerial competencies for multinational businesses - Lopez-Fernandez, Macarena, 1980-; Romero-Fernandez, Pedro M., 1956- (Business Science Reference, 2019)
"This book explores the skills of successful management: being a good communicator, creative, capable of facilitating team work, harmonizing different points of view, managing projects and meetings, and being able to listen are skills and aptitudes. It focuses on knowing which competences and skills will make it possible for managers to develop efficiently in an international company"--